1999
DOI: 10.1115/1.2830570
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Load Electrolytic Dressing With Bronze Bonded Grinding Wheels

Abstract: In electrolytic in-process dressing (ELID), a metal-bonded grinding wheel is dressed as a result of anodic dissolution. In this paper we describe experiments to evaluate the potential for ELID on bronze wheels in fixed-load grinding applications. A constant-force grinding apparatus was used to determine appropriate ELID conditions for a 10–20 μm bronze bonded diamond grinding wheel used to machine silicon carbide. A practical implementation of ELID was demonstrated using a low speed bronze bonded diamond wafer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…The grinding characteristics can also be influenced to a considerable extent by the composition of the grinding wheel. Bifano [9] has demonstrated the general suitability of bronze bonding materials for ELID grinding, although the different types of bronze bond were not investigated in detail.…”
Section: Advantages Of Bronze Bonded Grinding Wheelsmentioning
confidence: 98%
“…The grinding characteristics can also be influenced to a considerable extent by the composition of the grinding wheel. Bifano [9] has demonstrated the general suitability of bronze bonding materials for ELID grinding, although the different types of bronze bond were not investigated in detail.…”
Section: Advantages Of Bronze Bonded Grinding Wheelsmentioning
confidence: 98%
“…Ohmori (112) proposed a new method for electrolytic in-process dressing (BUD) of metal-bond wheels and discussed the application of this method for ceramic grinding. Bifano et al (113) and Welch et al (114) described the use of electrolytic in-process dressing for bronze-bond diamond wheels in fixed-load grinding operation on silicon carbide. They indicated that the rates of film growth, film wear, and diamond wear were the controlling factors in designing a successful EUD process.…”
Section: Wheel Truing and Dressingmentioning
confidence: 99%
“…A first attempt to model the layer growth (and wear) using a resistor as electrical equivalent of the layer was done by Bifano et al (1999). With this law it is theoretically possible to predict both the wear of the wheel bonding and the growth of the passivation layer.…”
Section: Introductionmentioning
confidence: 99%